2013
DOI: 10.3109/08820139.2013.854378
|View full text |Cite
|
Sign up to set email alerts
|

Study of TLR4 and IL-8 Gene Polymorphisms inH.pylori-Induced Inflammation in Gastric Cancer in an Ethnic Kashmiri Population

Abstract: No correlation was found between the appearance of disease and HP infection or the presence of TLR4 and IL-8 gene polymorphisms and HP infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
2
22
0
1
Order By: Relevance
“…Given that some authors have failed to show specific associations between polymorphisms in the TLR signaling pathway, especially in TLR2, TLR4 , and CD14 , and gastric precancerous lesions/GC (157, 160, 162, 164, 172, 174178, 180–183, 185, 188, 189), we performed the first global meta-analysis to assess the role of TLR2, TLR4 , and CD14 polymorphisms in gastric carcinogenesis (155), in an attempt to clarify the limited and current conflicting evidence, and to establish the true impact of the TLR signaling pathway in GC. Our meta-analysis, which included 18 case–control studies conducted in Caucasian, Asian, and Latin American populations, showed that TLR4 Asp299Gly was a definitive risk factor for GC in Western populations (pooled OR: 1.87, 95% CI: 1.31–2.65).…”
Section: Toll-like Receptors and Helicobacter Pylori-related Gastric mentioning
confidence: 99%
“…Given that some authors have failed to show specific associations between polymorphisms in the TLR signaling pathway, especially in TLR2, TLR4 , and CD14 , and gastric precancerous lesions/GC (157, 160, 162, 164, 172, 174178, 180–183, 185, 188, 189), we performed the first global meta-analysis to assess the role of TLR2, TLR4 , and CD14 polymorphisms in gastric carcinogenesis (155), in an attempt to clarify the limited and current conflicting evidence, and to establish the true impact of the TLR signaling pathway in GC. Our meta-analysis, which included 18 case–control studies conducted in Caucasian, Asian, and Latin American populations, showed that TLR4 Asp299Gly was a definitive risk factor for GC in Western populations (pooled OR: 1.87, 95% CI: 1.31–2.65).…”
Section: Toll-like Receptors and Helicobacter Pylori-related Gastric mentioning
confidence: 99%
“…As a result, it has been postulated that the presence of these mutations may influence the development of GI disease only within certain populations. 115 It is unknown whether other CXCL8 gene polymorphisms contribute to the development of certain GI diseases. Research to date examining the relationship between CXCL8 gene polymorphisms and GI disease has focused on the −251 region, and additional research is required to clarify whether polymorphisms at other sites also factor into susceptibility to GI inflammation or cancer.…”
Section: Cxcl8 Gene Polymorphismsmentioning
confidence: 99%
“…Лише у 13-15 % пацієнтів повністю відновлюється СО шлунка піс-ля ЕТ, у решти роками спостерігаються запальні зміни, з них приблизно у чверті -виражені [10]. Перебіг постерадикаційного запалення визначається особливостями міжклітинних взаємодій запального інфільтрату і епітелію СО шлунка [11].…”
Section: обговорення результатів дослідженняunclassified